Pengaruh Kualitas Produk Dan Online Customer Revie Terhadap Kepuasan Pelanggan Pada E-Commerce Tokopedia - Agriawan, Azmi; Rahmi, Palupi Permata; Muttaqin, Ridlwan (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
This study aims to determine how much influence product quality and online customer reviews have on Tokopedia e-commerce customer satisfaction. The sample used was 100 respondents. This study uses validity test, correlation coefficient test, determination coefficient test, multiple linear regression analysis and hypothesis testing compiled using SPSS. Based on the results of descriptive analysis, it can be seen that the variables Y, X1 and X2 are included in the excellent category. the results of the coefficient of determination show that the contribution of customer quality to customer satisfaction is 85.6%, the remaining 14.4%, influenced by other factors not examined. In addition, from the results of the study it, can be seen that the variables of product quality (X1) and online customer review (X2) partially affect customer satisfaction (Y). Simultaneously, product quality variables (X1), and online customer reviews (X2) have an effect on customer satisfaction (Y).